State, market and the crisis in Raniganj coal belt - Lahiri-Dutt, Kuntala (1999)
The recent decision to close down 64 `uneconomic' collieries in ECL's jurisdiction would render 72,000 people unemployed, besides hurting the economy of the Raniganj coal belt. The decision was apparently triggered by an ICICI report which has found that ECL's losses are concentrated in its underground mines. This article takes issue with the report and suggests that the proposed closure could be the first step towards privatisation of coal mining. - Reproduced
Keywords: Coal industry